2 Tunnelled peritoneal catheters for recurrent ascites in a specialist palliative care unit. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Thorpe, Kirsty; McKnight, Jamie; Kolb, Hildegard; McCullough, Claire; Morgan, Tim
Abstract : Introduction: NICE recommend the use of tunnelled peritoneal catheters (TPCs) for individuals with malignant ascites likely to require repeated paracentesis for symptom palliation. TPCs can avoid significant fluid build-up, improve quality of life (QOL) and reduce hospital admissions. TPCs are not commonly considered for patients with end-stage liver disease (ESLD). In NHS Grampian, TPCs are inserted by Palliative Medicine consultants in Roxburghe House Specialist Palliative Care Unit. Methods: Retrospective data collection and analysis for patients who underwent TPC insertion in Roxburghe House between 2014–2019 Patient outcomes were assessed. The number of temporary drains/hospital admissions prevented by TPC insertion was estimated. Results: 96 patients had a TPC inserted in Roxburghe House between 2014–2019. Diagnosis: 83% malignancy, 11% cirrhosis, 6% malignancy & cirrhosis. TPC remained in place for a mean of 67 days (64 in malignant, 90 in cirrhotic) with a range of 2–287 days. Mean time from procedure to death was 67 days (65 in malignant, 100 in cirrhotic). 33% died within 1 month of TPC insertion, although this group had no adverse prognostic indicators. 9% had major complications (systemic infection, possible perforation, bleed). 8% had minor complications (local infection, dislodgement). Complications rates were lower in the cirrhotic population. An estimated 301 temporary drains were prevented by TPC insertion. The average admission for temporary drain was 6 days, equating to 1, 806 days in hospital saved. Conclusions: TPC insertion is an effective management option for palliative patients with refractory ascites, and reduces hospital admissions in the last months of life. Although NICE guidance recommends TPC only for malignant ascites, this study shows low complication rates in the cirrhotic population. TPC should therefore also be considered for patients with ESLD who are ineligible for liver transplant. Further work is required to assess the impact of TPCs on QOL.